PENDIDIKAN ISLAM SEBAGAI PENGGERAK PERUBAHAN SOSIAL - Jelsa Yane Putri; Fauzana Annova (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
Islamic education has a significant role in encouraging positive social change. This article explains how Islamic education is not just a process of learning religious values but also has a role as the main driver for changing the paradigm, behavior and social life of society. By understanding Islamic teachings about education as an instrument of change, this article also explains the contribution of Islamic education in empowering society, overcoming social problems and forming characters with integrity. The method used is a kind of information from the library. Aims to discover several aspects, starting from the concept of Islamic education, community empowerment through education, the role of religious values in overcoming social problems, to the practical implementation of Islamic education in contemporary social contexts. In the context of contemporary challenges, this article highlights how Islamic education responds to and overcomes various contemporary problems including globalization, social injustice and intercultural and interreligious conflicts. By exploring the role of Islamic education in promoting the values of tolerance, concord and harmony, this article emphasizes the importance of implementing religious teachings in society to drive sustainable and positive social change.